Prediction of take-over time in highly automated driving by two psychometric tests (2015)
In this study, we investigated if the driver’s ability to take over vehicle control when being engaged in a secondary task (Surrogate Reference Task) can be predicted by a subject’s multitasking ability and reaction time. 23 participants performed a multitasking test and a simple response task and then drove for about 38 min highly automated on a highway and encountered five take-over situations. Data analysis revealed significant correlations between the multitasking performance and take-over time as well as gaze distributions for Situations 1 and 2, even when reaction time was controlled. This correlation diminished beginning with Situation 3, but a stable difference between the worst multitaskers and the best multitaskers persisted. Reaction time was not a significant predictor in any situation. The results can be seen as evidence for stable individual differences in dual task situations regarding automated driving, but they also highlight effects associated with the experience of a take-over situation.